Cyclin G2, a novel target of sulindac to inhibit cell cycle progression in colorectal cancer - Hongyou Zhao; Bin Yi; Zhipin Liang; Ches’Nique Phillips; Hui-Yi Lin; Adam I. Riker; Yaguang Xi (Genes and Diseases, 2021)
Sulindac has shown significant clinical benefit in preventing colorectal cancer progression, but its mechanism of action has not been fully elucidated. We have found that sulindac sulfide (SS) is able to inhibit cell cycle progression in human colorectal cancer cells, particularly through G1 arrest. To understand the underlying mechanisms of sulindac inhibitory activity, we have demonstrated that Cyclin G2 up-regulation upon SS treatment can substantially delay cell cycle progression by enhancing the transcriptional activity of FOXO3a in human colorectal tumor cells. MiR-182, an oncogenic microRNA known to inhibit FOXO3a gene expression, is also involved in the suppressive effect of SS on cell cycle progression. This process begins with the down-regulation of miR-182, followed by the enhancement of FOXO3a transcriptional activity and the up-regulation of Cyclin G2. To further determine the clinical utility of this axis, we analyzed the expression of miR-182/FOXO3a/Cyclin G2 in human colorectal tumor samples. Our results show not only that there are significant differences in miR-182/FOXO3a/Cyclin G2 between tumors and normal tissues, but also that the synergetic effect of miR-182 and FOXO3a is associated with predicting tumor progression. Our study demonstrates a novel mechanistic axis consisting of miR-182/FOXO3a/Cyclin G2 that mediates sulindac inhibition of cell cycle progression.